Analysis of the tomb Cemetery Municipal Garden of Maringa, state of Paraná - Martim, Aline Giseli; Angelis, Bruno Luiz Domingos de; Angelis Neto, Generoso de; Silva, Frederico Fonseca da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Based on the assumption that the burial of bodies and their subsequent decomposition into horizontal cemeteries can potentially cause contamination of groundwater, this paper aims to analyze the structural characteristics of the tombs and the tombs of architecture Garden Municipal Cemetery of Maringa, located in the Parana State (Brazil), from the identification of different types of architecture. Thus, the preparation of this article was focus on compliance with Municipal Decree no 100/1984 and no 1475/2002 approving the Regulation of Garden City Cemetery, in addition to regulating the coating and reconstructions of tombs in the same.